2019
DOI: 10.1002/jccs.201900176
|View full text |Cite
|
Sign up to set email alerts
|

Corrole‐based photodynamic antitumor therapy

Abstract: Study of photodynamic therapy (PDT) based on corroles has become one of the most important topics in corrole chemistry. Advances in synthetic methodology have made it possible for the preparation of structurally diverse corrole photosensitizers. This review covers the recent progress in the study of corrole as a photosensitizer in the photodynamic antitumor therapy. The content is organized in three sections: cellular uptaking and localization of corrole in tumor cells; morphological changes and cytotoxicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The chemical, physical and photophysical properties of corroles make them valuable photosensitizers for PDT. Therefore, the development of photosensitizers based on the corrole macrocycle has attracted the attention of several research groups and some review articles on this topic have been published [ 9 , 19 , 20 , 75 ]. Herein, the compilation of the latest advances is presented.…”
Section: Corroles As Pdt Agents In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical, physical and photophysical properties of corroles make them valuable photosensitizers for PDT. Therefore, the development of photosensitizers based on the corrole macrocycle has attracted the attention of several research groups and some review articles on this topic have been published [ 9 , 19 , 20 , 75 ]. Herein, the compilation of the latest advances is presented.…”
Section: Corroles As Pdt Agents In Cancer Treatmentmentioning
confidence: 99%
“…Their free-bases and metal complexes have been explored in a wide range of applications [ 8 , 9 ], namely as promising drug candidates for prevention and treatment of diverse diseases, such as diabetes, neurodegenerative diseases and cancer [ 10 , 11 , 12 , 13 , 14 ], as antibacterial agents [ 15 ] as well as bio-imaging agents [ 16 ]. Corroles also found application in the photodynamic inactivation of microorganisms (PDI) [ 17 ], sonodynamic therapy [ 18 ] and photodynamic therapy (PDT) [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have been reported with a quite exhaustive state-of-the-art utilization of freebase or metalated corroles as photosensitizers in cancer photodynamic therapy. 13,213,[223][224][225][226][227][228][229][230][231][232][233][234] Different A 3 -and trans-A 2 B-corroles were synthesized and their gallium complexes were prepared and studied as potential photosensitizers in PDT (Fig. 87).…”
Section: Photodynamic Therapy (Pdt) Applicationsmentioning
confidence: 99%
“… 1 5 Recently, porphyrin analogues such as corroles 6 , 7 have also proved promising as anticancer compounds. 8 , 9 Several families of 5d metallocorroles (including ReO, 10 OsN, 11 Ir, 12 Pt, 13 and Au 14 17 corroles) that we and others have studied in recent years are relevant in this connection. Although they were originally of interest primarily as curious, size-mismatched metal–ligand assemblies, their photophysical properties, especially near-infrared (NIR) phosphorescence under ambient conditions, now promise a wide range of practical applications, 18 , 19 such as in oxygen sensors, photodynamic therapy, and dye-sensitized solar cells and for triplet–triplet annihilation upconversion.…”
Section: Introductionmentioning
confidence: 96%